(untitled) (Research, Society and Development, 2020)
This paper presents the pedagogical strategy Field trips as a proposal for the teaching of Mathematics subject content in Elementary School. Initially, an experience of an ecological trail is reported in Parque Witeck, located in Novos Cabrais/RS, during the course “Field Trips in Environmental Education applied to the Exact Sciences”, from the Professional Master in Exact Sciences Teaching, from a State University of Rio Grande do Sul/Brazil. At the end of the trail the class was divided into small groups and as an activity they should develop teaching and learning strategies based on the theme: Field Trips, relating to subjects worked on in Basic Education. Following, three possible activities are proposed to be explored in the Mathematics Teaching of the 7th, 8th and 9th grades of Elementary School, namely: fractals, symmetry and trigonometry, respectively. It is hoped with the proposals made, that teachers will be encouraged, by reading this article, to include Field Trips in their planning, realizing that these non-formal spaces are conducive to teaching in all areas of knowledge.